RELASI ANTARA PERNIKAHAN DINI DAN PUTUS SEKOLAH PADA REMAJA PEREMPUAN DI KELURAHAN BEBANGA - Rusmayana M; Muzakkir Tayyibe; Wahyuddin Misbahuddin; Musdalifah Musdalifah; Muh. Fadhil Zakius Silmi Al-haq (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
Marriage is a bond of body and soul aimed at forming a sakinah, mawaddah, and rahmah family, but social reality shows a high rate of early marriages that deviate from the ideal age limits according to Law No. 16 of 2019 and psychological perspectives. This study aims to explore the causes and impacts of early marriage, particularly those occurring in Bebanga Village, Kalukku District. The research method used is descriptive qualitative with data collection techniques through observation and interviews with community leaders and educators. The results of the study indicate that early marriage is triggered by various complex factors, including economic limitations, low education levels, local customary traditions, as well as married by accident (MBA) factors due to unsupervised free association by parents. Field findings indicate that the normalization of interactions between the opposite sexes and the lack of parental understanding of long-term impacts are the main causes of the increase in marriage rates each year. Early marriage has significant impacts on women's reproductive health risks, an increase in school dropouts, and mental unpreparedness in taking on household responsibilities. As a solution, this study emphasizes the importance of intensive education for parents regarding child-rearing according to religious law and strengthening oversight of adolescent interactions to minimize future legal and social consequences. Through this research, it is hoped that society can be wiser in understanding the essence of marriage as a long-term act of worship that requires both physical and psychological maturity.